A compensatory fuzzy approach to multi-objective linear supplier selection problem with multiple-item - Ozkok, Beyza Ahlatcioglu; Tiryaki, Fatma (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Supplier selection problem is a multi-criteria decision making problem which includes both qualitative and quantitative factors. In the selection process many criteria may conflict with each other, therefore decision-making process becomes complicated. In this paper, we propose a compensatory fuzzy approach to solve multi-objective linear supplier selection problem with multiple-item (MLSSP-MI) by using Werners' fuzzy and (mu(and)) operator. The compromise solutions obtained by using fuzzy and (mu(and)) operator a are both compensatory and strongly efficient for our MLSSP-Ml. To our knowledge, combining compensatory (mu(and)) operator with MLSSP-MI has not been published up to now. Our compensatory fuzzy approach was explained on a case study. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Compensatory operators; Fuzzy mathematical programming; Multi-criteria decision; Supplier selection; Supply chain; VENDOR SELECTION; DECISION-MAKING; TOPSIS; Computer Science; Engineering; Operations Research & Management Science